Features of the activities of the first Gymnastic Society in the Kharkiv province at the end of the XIX and beginning of the XX century - Larysa Taran (Kharkiv State Academy of Physical Culture, 2019)
Purpose: to establish the features and areas of activity for the development of physical culture and sports in the territory of the Kharkіv province of the 1st Gymnastic Society. Material & Methods: the research material was preserved in rare editions - reports on the activities of the Kharkiv Gymnastic Society for 1895, 1896, 1900, 1909. Research methods: analysis and synthesis of scientific literature data, problem-search, historical-systemic and logical methods. Results: revealed that at the end of the 19th and the beginning of the 20th centuries, sports spread in large cities, and educational institutions and sports societies became the basis for the development of physical culture and sports. Kharkiv 1st Gymnastic Society began to work one of the first in the Kharkiv region. The use of various forms of organization of classes made it possible to carry out extensive campaigning among the population of Kharkiv to attract physical education and sports, including women and children; contribute to the development of sports that the Society has cultivated. Conclusions: as a result of the study, the year of foundation and founders of the 1st Gymnastic Society was established. The results of previous scientific studies on the functioning of societies at the end of the 19th and beginning of the 20th centuries were expanded in the following areas: organizational structure and composition, functions of a teacher (trainer), attracting women and children to physical education, sources of income and expense items, timetable and forms of organization of classes , activities for the development of physical education and individual sports in the territory of Kharkiv province, the 1st Gymnastic Society.